Peran dan Pola Asuh Orang Tua Terhadap Tingkah Laku Anak - Matondang, Fatiha Sabila Putri; Jahwa, Elvina; Habib, Miftahul Hasanah; Nasution, Naufal Ariq; Hambali, Luthfi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to educate parents about how good parenting and the role of parents in the growth and emotional development of children which is very important in influencing children's character and behavior in the future. The research method used is a research method with a qualitative approach using the library research method. This research uses secondary data sources from scientific articles and journals, relevant books. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of this study show that the role of parents in educating and nurturing children is very broad and complex. Through formal and informal education, character building, emotional support, social skills development, discipline application, and active involvement in daily life. It is important for parents to realize that their every action and decision will have a long-term impact on their children. The important role and good parenting in the formation of children's character and behavior include obedience, independence, empathy, and the ability to overcome stress so that when they grow up, children can become good individuals for their surroundings and the wider community, for that parents are expected to improve the quality of parenting in the family